Myzus persicae (Homopter: Aphididae) and Capsicum annuum (Solanaceae) volatiles: their effect on predators attraction - Ciarla, M.V.=700 1 Mareggiani, G.; Heit, G.; Puhl, L.
(En, Es)
ilus., 11 ref.
Keywords: MYZUS PERSICAE; CAPSICUM ANNUUM; GASES; CONTROL BIOLOGICO; ERIOPHYES; ESPAÑA; CYCLONEDA SANGUINEA; HARMONIA AXYRIDIS